Physical activity unveils the relationship between mitochondrial energetics, muscle quality, and physical function in older adults. Issue 2 (24th January 2018) - Distefano, Giovanna; Standley, Robert A.; Zhang, Xiaolei; Carnero, Elvis A.; Yi, Fanchao; Cornnell, Heather H.; Coen, Paul M.
Abstract : Background: The concept of mitochondrial dysfunction in ageing muscle is highly controversial. In addition, emerging evidence suggests that reduced muscle oxidative capacity and efficiency underlie the aetiology of mobility loss in older adults. Here, we hypothesized that studying well‐phenotyped older cohorts across a wide range of physical activity would unveil a range of mitochondrial function in skeletal muscle and in turn allow us to more clearly examine the impact of age per se on mitochondrial energetics. This also enabled us to more clearly define the relationships between mitochondrial energetics and muscle lipid content with clinically relevant assessments of muscle and physical function. Methods: Thirty‐nine volunteers were recruited to the following study groups: young active (YA, n  = 2 women/8 men, age = 31.2 ± 5.4 years), older active (OA, n  = 2 women/8 men, age = 67.5 ± 2.7 years), and older sedentary (OS, n  = 8 women/11 men, age = 70.7 ± 4.7 years). Participants completed a graded exercise test to determine fitness (VO2 peak), a submaximal exercise test to determine exercise efficiency, and daily physical activity was recorded using a tri‐axial armband accelerometer. Mitochondrial energetics were determined by (i) 31 P magnetic resonance spectroscopy and (ii) respirometry of fibre bundles from vastus lateralis biopsies. Quadriceps function was assessed by isokinetic dynamometry and physical function by the short physical performance battery and stair climb test. Results: Daily physical activity energy expenditure was significantly lower in OS, compared with YA and OA groups. Despite fitness being higher in YA compared with OA and OS, mitochondrial respiration, maximum mitochondrial capacity, Maximal ATP production/O xygen consumption (P/O) ratio, and exercise efficiency were similar in YA and OA groups and were significantly lower in OS. P/O ratio was correlated with exercise efficiency. Time to complete the stair climb and repeated chair stand tests were significantly greater for OS. Interestingly, maximum mitochondrial capacity was related to muscle contractile performance and physical function. Conclusions: Older adults who maintain a high amount of physical activity have better mitochondrial capacity, similar to highly active younger adults, and this is related to their better muscle quality, exercise efficiency, and physical performance. This suggests that mitochondria could be an important therapeutic target for sedentary ageing associated conditions including sarcopenia, dynapenia, and loss of physical function.